2006
DOI: 10.1007/s10517-006-0320-z
|View full text |Cite
|
Sign up to set email alerts
|

Cl− conduction of GABAA receptor complex on synaptic membranes in rat cortex at the early stage of chronic cerebral epileptization

Abstract: Experiments on Wistar rats showed that muscimol-stimulated Cl(-) conduction of synaptoneurosomes, isolated from the cerebral cortex increased after 5-day systemic treatment with subconvulsive doses of pentylene tetrasole during the initial stage of pharmacological pentylene tetrasole kindling, characterized by gradually augmenting convulsive readiness of the brain. This indicates an increase in functional activity of the GABA(A) receptor/Cl(-) ionophore complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Changes in functional activity of GABA A -RC in synaptoneurosomes of rat brain cortex at different stages of PTZkindling were demonstrated (including our previous results, Fig. 2) [5][6][7][8]. The basal and muscimolstimulated 36 Cl -entry into synaptoneurosomes increased at the early stage of kindling.…”
Section: Resultsmentioning
confidence: 56%
“…Changes in functional activity of GABA A -RC in synaptoneurosomes of rat brain cortex at different stages of PTZkindling were demonstrated (including our previous results, Fig. 2) [5][6][7][8]. The basal and muscimolstimulated 36 Cl -entry into synaptoneurosomes increased at the early stage of kindling.…”
Section: Resultsmentioning
confidence: 56%
“…At the early stage of kindling (in the absence of seizures) the pathological process of epileptogenesis is preceded by activation of protective sanogenetic mechanisms (antiepileptic processes). Seizures do not develop when these processes are in the active state [7,9]. Antiepileptic mechanisms are suppressed, while the intensity of proepileptic processes increases during the intermediate and final stage of kindling.…”
Section: Resultsmentioning
confidence: 99%
“…This effect was more pronounced in delayed periods of kindling and was accompanied by enhancement of epileptiform signs on EEG.The model of corasol kindling (CK) reproduces peculiarities of chronic epileptization of the brain and the most important pathogenetic mechanisms underlying the development of long-lasting changes in the excitability of brain structures [3][4][5]. A close relationship between the mechanisms of regulation of immunological reactivity and control of the functional state of the nervous tissue was demonstrated [4,7].…”
mentioning
confidence: 99%
“…A close relationship between the mechanisms of regulation of immunological reactivity and control of the functional state of the nervous tissue was demonstrated [4,7]. For instance, it was shown that IL-1β suppresses kainite-provoked epileptogenesis in various brain structures, while blockade of IL-1β receptors arrests pathologically enhanced excitation of neuronal formations [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation